How effective are the sustainability criteria accompanying the European Union 2020 biofuel targets? - Frank, S.; Böttcher, Hannes; Havlík, Petr; Valin, Hugo; Mosnier, Aline; Obersteiner, Michael; Schmid, Erwin; Elbersen, B. (Wiley, 2013)
The expansion of biofuel production can lead to an array of negative environmental impacts. Therefore, the European Union (EU) has recently imposed sustainability criteria on biofuel production in the Renewable Energy Directive (RED). In this article, we analyse the effectiveness of the sustainability criteria for climate change mitigation and biodiversity conservation. We first use a global agriculture and forestry model to investigate environmental effects of the EU member states National Renewable Energy Action Plans (NREAPs) without sustainability criteria. We conclude that these targets would drive losses of 2.2 Mha of highly biodiverse areas and generate 95 Mt CO 2 eq of additional greenhouse gas (GHG) emissions. However, in a second step, we demonstrate that the EU biofuel demand could be satisfied 'sustainably' according to RED despite its negative environmental effects. This is because the majority of global crop production is produced 'sustainably' in the sense of RED and can provide more than 10 times the total European biofuel demand in 2020 if reallocated from sectors without sustainability criteria. This finding points to a potential policy failure of applying sustainability regulation to a single sector in a single region. To be effective this policy needs to be more complete in targeting a wider scope of agricultural commodities and more comprehensive in its membership of countries.